HUBUNGAN PEMAKAIAN ALAT DAN OBAT KONTRASEPSI SUNTIKAN DENGAN GANGGUAN MENSTRUASI DI KLINIK NIRMALA - Sinaga, Elvina Sari (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACTAccording to the World Health Organization (WHO) there are nearly 380 million couples running Family planning. This research is a analttic survey with cross sectional design that is to know the relation of usage of contraception tool and contraception with menstrual disorder,sampling this research using accidental sampling that is sampling method by chance coincidence. In 85 out of 85 cases of mother using 1 month injection of polimenore/spooting injection were 50 cases (100%) while mothers using 3 Months of injectable amenorrhea (65,71%) had Spotted 12 case (34,29%) ini clinic Nirmala. Result of statistical test by using chi square test got p value =0,01<0,05 and X2 = 41,77 mean there is relation of tool usage and contraceptive injection drug with menstrual disorder 95% CI level equal to 1,84-4,61 meaning mothers who used injectable contraceptive devices 1-4 times experianced a menstrual disorder at the Nirmala ClinicKeyword: Contraceptive Injection, Medication